PENGARUH PENGALAMAN AUDITOR, SKEPTISISME PROFESIONAL DAN TEKANAN WAKTU TERHADAP PENDETEKSIAN KECURANGAN DI PERWAKILAN BPKP PROVINSI BALI - susandya, Anak Agung Putu Gede Bagus Arie; Suryandari, Ni Nyoman Ayu (Jurnal Akuntansi dan Keuangan, 2021)
Today's technological and economic developments can be said to be like a double-edged knife. On the one hand, this development not only has a positive impact on the progress of a country but can also become a stumbling block due to fraud committed by parties who want to get a profit. The crime of fraud is increasingly varied following the creativity of the perpetrators of fraud in the form of misuse of economics and information technology. Fraud has increased rapidly among companies, organizations and even government agencies.This study aims to determine the effect of auditor experience, professional skepticism and time pressure at the Representative Office of the Financial and Development Supervisory Agency (BPKP) Bali Province. The number of samples taken was 66 respondents who were determined by purposive sampling method. All data obtained from distributing questionnaires is suitable for use, then analyzed by multiple linear regression.The results of this study indicate that the experience of auditors and professional skepticism has a positive effect on fraud detection at BPKP Representatives in Bali Province. Meanwhile, time pressure has no effect on fraud detection at BPKP Representatives of Bali Province. Future research can develop this research by using other variables which in theory have an influence on fraud detection.Â